2004
DOI: 10.1111/j.1523-1755.2004.00523.x
|View full text |Cite
|
Sign up to set email alerts
|

Model-based study of the effects of the hemodialysis technique on the compensatory response to hypovolemia

Abstract: The increased risk of acute hypotension in BD compared to AFB is caused by a therapy-induced inhibition of reflex compensatory response to hypovolemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 40 publications
(42 reference statements)
1
37
0
Order By: Relevance
“…The better intradialytic cardiovascular stability associated with AFB may conceivably be related to several factors: those peculiar to the hemodiafiltration techniques (which combine an enhanced removal of the higher molecular weight solutes with a more biocompatible system) [39]), though this may be questionable because the small substitution volume should only marginally affect middle molecule removal; the use of high-flux membrane (though in our study AFB coincided with a lower IH rate than BD regardless of membrane flux); the (albeit small) convective component (consistent with the results of a recent randomized controlled study [26] showing that online hemofiltration and hemodiafiltration reduce symptomatic IH in the long term); the absence of acetate in the bath and the infusate (since it has been demonstrated that even small amounts of this solute in the dialysate may impair cardiovascular reactivity [39]), and/or a thermal effect induced by the bicarbonate solution infused in the postdilution mode [39] since it is well known that a cold dialysate and/or infusate reduces the frequency of IH [40] (though this should not be a major contributor in our study since the infusate for AFB was usually warmed to a temperature similar to that of the dialysate and its infusion rate was always <15% of the prescribed Q b ). Moreover, our study strongly suggests that the beneficial effects by AFB are unrelated to changes in intradialytic ultrafiltration and dry weight, since these parameters did not vary within or between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The better intradialytic cardiovascular stability associated with AFB may conceivably be related to several factors: those peculiar to the hemodiafiltration techniques (which combine an enhanced removal of the higher molecular weight solutes with a more biocompatible system) [39]), though this may be questionable because the small substitution volume should only marginally affect middle molecule removal; the use of high-flux membrane (though in our study AFB coincided with a lower IH rate than BD regardless of membrane flux); the (albeit small) convective component (consistent with the results of a recent randomized controlled study [26] showing that online hemofiltration and hemodiafiltration reduce symptomatic IH in the long term); the absence of acetate in the bath and the infusate (since it has been demonstrated that even small amounts of this solute in the dialysate may impair cardiovascular reactivity [39]), and/or a thermal effect induced by the bicarbonate solution infused in the postdilution mode [39] since it is well known that a cold dialysate and/or infusate reduces the frequency of IH [40] (though this should not be a major contributor in our study since the infusate for AFB was usually warmed to a temperature similar to that of the dialysate and its infusion rate was always <15% of the prescribed Q b ). Moreover, our study strongly suggests that the beneficial effects by AFB are unrelated to changes in intradialytic ultrafiltration and dry weight, since these parameters did not vary within or between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The measured values were taken from the bibliography and represent the mean systolic blood pressure from 32 hemodialysis patients [19]. We remark that the global walk of the three curves is the same A complete validation of the model necessitates to compare the other parameters to those measured, which is a handicap.…”
Section: Resultsmentioning
confidence: 99%
“…At the core of IDH is uncompensated response to reduction in circulating blood volume [40]. The patient may exhibit a blunted response to this reduction or the reduction may be too large to mount an effective response.…”
Section: Treatment For Intradialytic Hypotensionmentioning
confidence: 99%